Snowflake Data Warehousing for Multi-Region BFSI Analytics - Niranjan Reddy Rachamala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The countless customer and transactional records are managed efficiently in the BFSI sector with the help of data warehousing. Since BFSI institutions are active in different regions, it is very important to have multi-region analytics that comply with rules. By using a cloud native system, Snowflake’s data warehouse splits storage from compute, offers flexibility, aids in securely sharing data, and follows key compliance rules. In this work, it analyze data collected from multiple sources to examine how Snowflake helps with distributed analytics in BFSI. The new findings show that Snowflake addresses key problems associated with old data warehousing systems by improving scalability, following regulations and making data available anywhere at any moment. The findings can be important for BFSI organizations working towards revamping their data analysis tools and making sure they follow regulations smoothly.